1995
DOI: 10.1002/nt.2620030208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of T‐2 toxin and verrucarin A in combination on Kluyveromyces marxianus

Abstract: The growth inhibitory effects of combinations of T-2 toxin and verrucarin A on the yeast Kluyveromyces marxianus was studied. A combination index value was derived to indicate the type of interaction that existed between the binary mixture of these two toxins at various ratios and the target yeast cells. The type of interaction was dependent on the ratio of the toxins used to attain a particular level of growth inhibition. Further, the least change in the type and intensity of interaction or the maximally quie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…The interactive effect of DON and NIV found in the present study was in agreement with some previous in vitro studies on yeast growth (Madhyastha et al, 1994) and on DNA syntheses in L929 cells (Tajima et al, 2002), although some reported additivity of trichothecenes (Thuvander et al, 1999). A plausible explanation for such discrepancies could be differences in the ratios of trichothecenes in the mixture, or to differences in effect levels (Jones et al, 1995;Koshinsky and Khachatourians, 1992). The possible interaction between ZEA and FB1 was not fully elucidated in the current stage.…”
Section: Combinations % Reduction In Cell Viabilitysupporting
confidence: 77%
“…The interactive effect of DON and NIV found in the present study was in agreement with some previous in vitro studies on yeast growth (Madhyastha et al, 1994) and on DNA syntheses in L929 cells (Tajima et al, 2002), although some reported additivity of trichothecenes (Thuvander et al, 1999). A plausible explanation for such discrepancies could be differences in the ratios of trichothecenes in the mixture, or to differences in effect levels (Jones et al, 1995;Koshinsky and Khachatourians, 1992). The possible interaction between ZEA and FB1 was not fully elucidated in the current stage.…”
Section: Combinations % Reduction In Cell Viabilitysupporting
confidence: 77%
“…Binary and ternary combinations of Type B trichothecenes were tested for interaction using the Chou-Talalay method (Chou, 2006). This method, already used to study other mycotoxin combinations (Koshinsky and Khachatourians, 1992;Jones et al, 1995;Ruiz et al, 2011) combines a qualitative assessment of interactions via an isobolographic analysis and a quantification of synergy or antagonism by calculating a combination index and dose reduction index at different effect levels. For the 50% cytotoxicity level, the isobolographic analysis indicates an additive effect of the toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Bien que Ie F. graminearum puisse produire simultané-ment plus d'une trichothécène, les effets additifs ou synergiques n'ont pas été décrits auparavant chez les végétaux supérieurs. Par contre, Jones et al (1995) ont rapporté Faction synergique du T2 et de la verrucarine A sur 1'inhibition de la croissance de cultures de levures {Kluyvero-myces marxianus). Le filtrat de culture que nous avons uti lise, contenant du DON et du 3-ADON, a fortement inhibé le développement des tissus de blé.…”
Section: Figunclassified